Zebrafish and Galleria mellonella: Models to Identify the Subsequent Infection and Evaluate the Immunological Differences in Different Klebsiella pneumoniae Intestinal Colonization Strains - Zhang, Xiucai; Zhao, Yajie; Wu, Qing; Lin, Jie; Fang, Renchi; Bi, Wenzi; Dong, Guofeng; Li, Jiahui; Zhang, Yizhi; Cao, Jianming; Zhou, Tieli (Frontiers in Microbiology, 2019)
The intestine is the main reservoir of bacterial pathogens in most organisms. Klebsiella pneumoniae is an important opportunistic pathogen associated with nosocomial bacterial infections. Intestinal colonization with K. pneumoniae has been shown to be associated with an increased risk of subsequent infections. However, not all K. pneumoniae strains in the intestine cause further infection, and the distinction of the difference among strains that cause infection after colonization and the ones causing only asymptomatic colonization is unclear. In this study, we report a case of a hospitalized patient from the ICU. We screened out two intestine colonization strains (FK4111, FK4758) to analyze the subsequent infection conditions. We set up infection models of zebrafish and Galleria mellonella to establish the differences in the potential for causing subsequent infection and the immunological specificities after K. pneumoniae intestine colonization. Sudan Black B and neutral red staining results indicated that FK4758 was more responsive to neutrophil recruitment and phagocytosis of macrophages than FK4111. The results of the assessment of the organ bacterial load revealed that FK4111 and FK4758 both had the highest bacterial loads in the zebrafish intestine compared to those in other organs. However, in the zebrafish spleen, liver, and heart, the FK4758 load was significantly higher than that of FK4111. The ST37 strain FK4111, which does not produce carbapenemase, did not cause infection after colonization, whereas the ST11 strain FK4758, which produces carbapenemase, caused infection after intestinal colonization. Our finding demonstrated that not all intestinal colonization of K. pneumoniae subsequently caused infections, and the infections of K. pneumoniae after colonization are different. Therefore, the infection models we established provided possibility for the estimation of host-microbial interactions.